2006
DOI: 10.1021/ma052736s
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Dependent Deformation Behavior of POSS-Filled and Plasticized Poly(vinyl chloride)

Abstract: Polymers are known to exhibit strong time-dependent mechanical behavior. In different temperatures or frequency regimes, the rate sensitivities of polymers change as various primary and secondary molecular mobility mechanisms are accessed. The incorporation of nanoparticles can potentially alter the molecular level structure of polymer, offering the opportunity to tailor the rate-dependent mechanical deformation and failure behavior of the polymer.This study focuses on polyhedral oligomeric silsesquioxanes (PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
7
44
1
Order By: Relevance
“…20 wt% for PPVC-2 versus 60 wt% for PPVC-6), the β-transition stays in approximately the same position at the lowest rate (0.035 s −1 or 1 Hz): the amount of plasticizer does not shift the approximate location of the β-transition, even though the α-transition shifts to a lower temperature once plasticizer is added (as expected). Thus, the addition of more phenyl rings (or DINP), which is understood to create additional free volume in the material [7,31,32], does not affect the location of the β-transition. Hence, the β-transition must include more than just the behaviour of phenyl rings (i.e.…”
Section: Time-temperature Superpositionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 wt% for PPVC-2 versus 60 wt% for PPVC-6), the β-transition stays in approximately the same position at the lowest rate (0.035 s −1 or 1 Hz): the amount of plasticizer does not shift the approximate location of the β-transition, even though the α-transition shifts to a lower temperature once plasticizer is added (as expected). Thus, the addition of more phenyl rings (or DINP), which is understood to create additional free volume in the material [7,31,32], does not affect the location of the β-transition. Hence, the β-transition must include more than just the behaviour of phenyl rings (i.e.…”
Section: Time-temperature Superpositionmentioning
confidence: 99%
“…Alternatively, the increased strength in more rubbery or elastomeric polymers is accounted for by the change in molecular mobility during the glass transition (or α-transition). These transitions are usually seen within polymers at lower temperatures, but can be shifted in temperature by changes in strain rate, as the transition increases in temperature with increasing strain rate [5][6][7][8].…”
Section: Introduction (A) Rate and Temperature Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Due to its interesting properties, various PVC composites have been prepared by dispersing double hydroxides [10], CaCO 3 [11,12], metal oxides [12], multiwall carbon nanotubes [13], C-60 [14], polyaniline, a conducting polymer [15], and silica [16,17]. Soong et al have reported the feasibility of using copper nanoparticledispersed PVC nanocomposites toward environmental remediation techniques, such as antifungal and bacteriostatic applications [18].…”
Section: Introductonmentioning
confidence: 99%
“…Further improvements on these models used a cooperative relaxation effect for segmental relaxation to reproduce new data on a range of polymers to high strain rates, while retaining an essentially thermodynamic approach (Richeton et al, 2005(Richeton et al, , 2006(Richeton et al, , 2007. Mulliken and Boyce (2006) demonstrated that the stress-strain response of PC and PMMA and PVC (Soong et al, 2006), can be linked back to their dynamic mechanical spectra. In particular, they show that the rate dependence of the aand b-transition loss peaks and storage modulus can be used to model the shifts in modulus and yield as a function of temperature and rate.…”
Section: Introductionmentioning
confidence: 99%